PROSEDUR PEMBIAYAAN,USAHA MIKRO BRI SYARIAH PT. BANK BRI SYARIAH TBK KCP SUDIRMAN PALEMBANG - Eriza Eriza; Nanda Nanda; Sinta Sinta; Siti Siti; Amir Salim (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Bank is a financial institution specifically functions as an agent of trust, agent of development, and agent of services. In order to collect funds from people who have a surplus of funds in the form of savings and then distribute them to people who need funds in the form of financing, of course, they really need trust from the community. Banking is an institution that has a major role in the development of a country. This role is manifested in the bank's function as a financial intermediary institution. Some people believe that the money saved will not be misused by the bank which will be managed properly so that the bank will not go bankrupt and at a certain time the community will be able to withdraw their savings from the bank. In addition to conducting fund-raising and channeling activities, banks offer banking services to the public, including in the form of money transfer services, deposit services for valuable goods, bank guarantee services and other services so that the bank has an agent of services. Conventional Banks are banks that carry out conventional business activities which in their activities provide services in their activities providing services based on the procedures and provisions set by the state. Conventional banks will accept all forms of investment in all business fields as long as they comply with predetermined requirements. Meanwhile, Sharia Banks are banks that carry out business activities based on sharia principles or Islamic legal principles as regulated in the fatwas of the Indonesian Ulema Council such as the principles of justice and balance ('adl wa tawazun), benefit (maslahah), universalism (alamyah), and do not contain gharar. masyir, usury, zalim and haram objects.